The COVID Virus Crisis Resurrects the Public Health Exception in EU Migration Law - De Bruycker, Philippe (Frontiers in Political Science, 2021)
One of the consequences of the covid-19 crisis is the reintroduction of controls at the external and internal borders of the EU Member States. This happened in disorder because the competent authority are each Member State despite decisions appear to be taken at the European level. Public health is not always foreseen as a legal basis for those measures, but they can be justified by the exceptional crisis comparable to a threat for public order. The measures taken are not only border controls but more precisely border closures more or less selective. Member States were supposed to cooperate between each other and with the European Commission when taking those measures. All persons (nationals, EU citizens and third-country nationals) were targeted) knowing that most of them have the right to return to their Member State of nationality or of residence. Borders measures have been quickly replaced by health measures so that the Schengen are is not at risk of collapsing.